Biology Teachers’ Academic Qualifications as a Predictor of ICT Skill Level on Pedagogical Approaches in North-Central, Nigeria - Akanbi Jimoh Abdulraheem; Hameed Olalekan Bolaji; Abdulmuhsin Ibrahim; Kafayat Ibironke Owolarafe; Mukhtar Dutsinma Lawal (Universitas Pendidikan Ganesha, 2025)
Despite the growing demand for digital competence in education, many biology teachers still face challenges in effectively integrating ICT into pedagogical practices. This study investigated biology teachers’ academic qualifications as a predictor of ICT skill levels in pedagogical approaches in north-central Nigeria. This research adopted a descriptive cross-sectional survey design to examine the influence of Biology teachers’ academic qualifications and ICT competencies on their instructional strategies within North-Central Nigeria. The study involved 696 Biology teachers from public secondary schools across six states and the Federal Capital Territory (FCT). A multi-stage sampling approach was employed, combining random and stratified techniques based on school type and teachers’ academic backgrounds. Data were gathered using a reliable and validated questionnaire that measured teachers’ ICT literacy, skill proficiency, and instructional practices. Responses were scored using a four-point Likert scale, and data analysis was conducted using descriptive statistics, independent samples t-tests, and ANOVA at a 0.05 significance threshold. The analysis revealed that professionally qualified biology teachers demonstrated significantly higher ICT competence compared to their less qualified peers, as shown by ANOVA results F(2, 692) = 11.14, p = 0.00. Therefore, it can be concluded that higher academic qualifications contribute to stronger ICT proficiency and the adoption of more student-centered teaching approaches. The study recommends targeted ICT training, continuous professional development, and high academic standards to improve biology education quality and inclusivity.